Structure development of diagnostic providing and diagnostic model of axle boxes in modern railroad cars - Петухов, Вадим Михайлович (Technology audit and production reserves, 2015)
The study of technical and informational characteristics of embedded control systems of axle boxes has allowed creating the overall structure of the diagnostic software for axle boxes for modern railroad cars and also apply a thermal model and the recognition of the technical condition of axle boxes for solving the problem of increasing the reliability of the control of the rolling stock when it moves, due to the recent increase in the speed of movement of the extended portion of non-stop movement, as well as an increase in the intensity of the operation of rolling stock. Based on these studies it was developed the overall structure of the diagnostic software for axle boxes of modern railroad cars. It offers the most informative diagnostic features of the technical condition of axle box, increasing the accuracy of control and reduces the impact of various types of interference in its results. It is built diagnostic model of axle box on the basis of the thermal model based on additional parameters, the measurement of which is technically feasible only embedded systems. The proposed structure of the diagnostic software for axle boxes will not only improve the reliability and efficiency of control, but also makes it possible to detect emerging defects in the early stages and to solve the actual problem of forecasting residual resource of axle box to reduce the number of uncoupling of defective railroad cars. Developed activities will help to improve traffic safety and stability of the transportation process.